Anthropometric and performance characteristics of Turkey National U-14 volleyball players - Ayan, V.; Bektas, Y.; Erol, A. E. (African Journal for Physical, Health Education, Recreation and Dance, 2012)
The main objective of this research was to determine the anthropometric, somatotype and performance characteristics of the Turkish National U-14 Female Volleyball Team that participated in the national team selection session. Fifty- eight (58) female volleyball players from various towns in Turkey camped to compete in the national team selection carried out at METU sports hall in 2007 participated in the study. Heath-Carter method was used to determine the somatotype characteristics. Correlate (bivariate) statistics was used to determine any relationships between the players` somatotypes and their performance measures. The mean age, height and weight values of the participants (n=58) were 14.38±0.98 years, 177.17±5.42 cm, 60.97±8.10 kg, respectively. The mean values of the performance evaluation tests including vertical jump, standing long jump, and 20 -metre run were 41.14±4,76 cm, 191.24±16,33 cm, and 3.78±,18 sec, respectively. The mean somatotype values of the players were as follows: endomorphy 3.44±0.98, mesomorphy 2.13±1.00, ectomorphy: 4.46±1.09. The research was helpful in providing a guide regarding the selection of female volleyball players as well as designing training programmes and plans related to specific player positions.